Culinary tourism, tourist routes and local products: the case of wine and cheese in Catalonia - Molleví Bortoló, Gemma; Fusté Forné, Francesc (Geographicalia, 2017)
Culinary tourism is a type of tourism whose practice occurs throughout the whole year, and in any geographical context. Tourist routes, both natural and cultural, represent a product that also contributes to reduce the seasonality of tourism, with wider potential for regional development.This article describes the case of food tourism in Catalonia regarding the offer of local products through tourist routes. Consequently, four cases of tourist and gastronomic routes around two particular products (wine, cheese) are studied. The highlighted routes reflect part of the great mosaic of rural tourism opportunities in Catalonia. These are linked to the empowerment and visibility of rurality, and to its economic impact. From a theoretical perspective, it usefully serves to the recovery and valorization of agricultural landscapes and cultural heritage, particularly the culinary.
Keywords: Catalonia; wine tourism; local products; tourist routes; culinary tourism.